Polysaccharides and Composite Adsorbents in the Spotlight for Effective Agrochemical Residue Removal from Water - Mónica Ortiz-Martínez; Brenda Restori-Corona; Luis Hernández-García; Diana Alonso-Segura (Macromol)
Agrochemical residues, including pesticides and herbicides, pose significant environmental and health risks when present in water sources. Conventional water treatment methods often fall short in effectively removing these persistent pollutants, necessitating innovative solutions. This review explores the use of polysaccharides and composite adsorbents as sustainable alternatives for agrochemical residue removal from water. Biopolymers such as chitosan, alginate, and cellulose are highlighted for their biodegradability, biocompatibility, and ability to be functionalized for enhanced adsorption performance. Recent advances in the development of composite materials incorporating nanomaterials, such as graphene, oxide, and metal oxides, have shown significant promise in enhancing the efficiency and selectivity of agrochemical adsorption. The review also addresses the fundamental mechanism of adsorption, such as electrostatic interactions, hydrogen bonding, and hydrophobic forces, that contribute to the effectiveness of these materials. Challenges associated with scalability, regeneration, and real-world applications are discussed, as well as future opportunities for integrating emerging technologies like 3D printing and machine learning into adsorbent design. Overall, polysaccharides and composites offer a promising pathway toward achieving efficient and sustainable agrochemical residue removal, with ongoing research needed to overcome current limitations and optimize their practical application in water treatment.